Paniker's textbook of medical parasitology - Paniker, C. K. Jayaram (Jaypee Brothers Medical Publishers (P) Ltd., 2013)
Fully revised, new edition providing undergraduate students with the most up to date information in the field of parasitology. Covers all key parasites and parasitic diseases. Includes review questions for revision.